2018
DOI: 10.3988/jcn.2018.14.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Phenotypic Spectrum of Multiple Sclerosis at a University Hospital in Saudi Arabia

Abstract: Background and PurposeThe objective of this study was to determine the frequencies of different clinical presentations and the phenotypic spectrum of multiple sclerosis (MS).MethodsThis cross-sectional study was performed in the Neurology Department of King Fahd Hospital of University Alkhobar in the Kingdom of Saudi Arabia (KSA). Data of 190 MS patients who fulfilled the McDonald criteria were retrieved from medical records and analyzed.ResultsThe age at disease onset was 26.27±8.2 years (mean±SD) and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In our study, 3.3% of patients with MS had SPMS and 3.3% had PPMS. A previous study found that 12.1% of patients with MS had SPMS, but only 2.6% had PPMS [ 23 ]. The likelihood of RRMS turning to SPMS can be reduced with early diagnosis and treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 3.3% of patients with MS had SPMS and 3.3% had PPMS. A previous study found that 12.1% of patients with MS had SPMS, but only 2.6% had PPMS [ 23 ]. The likelihood of RRMS turning to SPMS can be reduced with early diagnosis and treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis was thought to be uncommon in Kingdom of Saudi Arabia, but the prevalence of MS is increasing in the Gulf region, particularly in Kingdom of Saudi Arabia, and the latest prevalence estimates are 40/100,000 in 2008. 1,2 These increasing numbers of MS patients represent a challenge to provide treatment, health promotion, employment, and rehabilitation for severely disabled patients. 3 The etiology of MS is still unknown.…”
mentioning
confidence: 99%
“…Relapsing-remitting multiple sclerosis was found in 85-90% of patients. In this MS clinical subtype was found the first manifestations in the form of spinal-cord symptoms, optic neuritis, brainstem and pyramidal tract symptoms [2].…”
Section: Introductionmentioning
confidence: 95%